2016
DOI: 10.18383/j.tom.2016.00211
|View full text |Cite
|
Sign up to set email alerts
|

Deep Feature Transfer Learning in Combination with Traditional Features Predicts Survival among Patients with Lung Adenocarcinoma

Abstract: Lung cancer is the most common cause of cancer-related deaths in the USA. It can be detected and diagnosed using computed tomography images. For an automated classifier, identifying predictive features from medical images is a key concern. Deep feature extraction using pretrained convolutional neural networks (CNNs) has recently been successfully applied in some image domains. Here, we applied a pretrained CNN to extract deep features from 40 computed tomography images, with contrast, of non-small cell adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 30 publications
1
77
0
Order By: Relevance
“…Previous literature on quantitative image-based prediction of OS has suggested that deep features play a complementary role to radiomics features. 12,14,22,23 Our study demonstrates that this remains true when using deep features extracted by VGG-19, an advanced model with documented excellent performance in image classification. Deep features are not limited to previously identified image attributes or even to those understandable by humans.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Previous literature on quantitative image-based prediction of OS has suggested that deep features play a complementary role to radiomics features. 12,14,22,23 Our study demonstrates that this remains true when using deep features extracted by VGG-19, an advanced model with documented excellent performance in image classification. Deep features are not limited to previously identified image attributes or even to those understandable by humans.…”
Section: Discussionmentioning
confidence: 60%
“…Under this circumstance, the transfer learning technique is introduced to apply CNN models from one field to another. For example, Paul et al 14,22 generated deep features from a pretrained CNN model to improve survival prediction accuracy for patients with lung cancer. Lao et al 12 adopted the pretrained CNN_S model for prediction of survival in GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the growing number of applications of deep learning in medical imaging 14 , several efforts have compared deep learning methods with their predefined feature-based counterparts and have reported substantial performance improvements with deep learning 34,35 . Studies have also shown that deep learning technologies are on par with radiologists’ performance for both detection 36 and segmentation 37 tasks in ultrasonography and MRI, respectively.…”
Section: Ai In Medical Imagingmentioning
confidence: 99%
“…Liu et al [ 52 ] applied the CNN-F architecture [ 53 ] pretrained on ILSVRC-2012 with the ImageNet dataset for predicting survival time based on brain MR images, achieving the highest accuracy of 95.45%. Paul et al [ 54 ] predicted short- and long-term survivors of non-small-cell adenocarcinoma lung cancer on contrast CT images, with 5 postrectified linear unit features extracted from a VGG-F pretrained CNN and 5 traditional features. They obtained an accuracy of 90% and AUC of 0.935.…”
Section: Deep Learning In Survival Predictionmentioning
confidence: 99%